Reducing radiation dose for a linear slot scanning digital X-ray machine using a filtration technique - Perks, Timothy David (Division of Biomedical Engineering, 2015)
This study describes the development of a filtration technique applied to the Lodox Statscan linear slotscanning digital X-ray system to reduce radiation dose to paediatric patients whilst preserving diagnostic image quality. The Statscan is an FDA approved, commercially available digital X-ray system commonly used for trauma and emergency patients. The Statscan provides significantly lower radiation dose to patients than conventional Xray systems for comparable studies without loss of image quality. This is particularly beneficial in paediatric radiology, where the risks associated with ionizing radiation are much higher. A static dose prediction model for the Statscan which was previously developed at the University of Cape Town has been adapted to create a dynamic dose prediction model which allows the user to adjust the system scanning parameters. The model calculates the patient entrance dose from an energy spectrum generated using the input parameters. The effective dose for a paediatric sized patient is then calculated using a Monte Carlo simulation. The dynamic model allows for variation of the scan parameters and direct observation of the expected dose levels for specific examinations. Filtration is a well-known technique for reducing radiation dose, where a filter material is placed in the path of the X-ray beam to reduce patient exposure to radiation. The dynamic model was used to design a new filtration technique for the paediatric settings on the Statscan.